KAJIAN LIQUID PENETRANT TEST (PT) DALAM NON DESTRUCTIVE TESTING (NDT) BERDASARKAN PRINSIP KERJA, DWELL TIME, DAN ACCEPTANCE CRITERIA MENGACU PADA STANDAR ASME DAN AWS - Rizwan, Muhammad Mifthahul; putra, Ricky cahyasari putra; Moh fawaid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Material testing is an essential stage in ensuring the quality and safety of engineering components, particularly in welded joints. One of the most widely used methods is Non-Destructive Testing (NDT), which is a testing technique that does not damage the material. This study aims to examine the Liquid Penetrant Test (PT) method as one of the NDT techniques used to detect surface defects in materials. The method employed in this study is a literature review based on various scientific references, including ASME and AWS standards. The study covers the working principles, inspection procedures, dwell time parameters, and acceptance criteria of the penetrant testing method. The results indicate that the PT method operates based on the capillary action phenomenon, where the penetrant liquid is able to enter small cracks or discontinuities on the material surface. The testing process consists of several main stages, including surface cleaning, penetrant application, penetration time (dwell time), excess penetrant removal, developer application, and visual inspection. Furthermore, the evaluation of test results is conducted based on ASME and AWS standards, which classify indications into linear and rounded indications. Linear indications are generally not acceptable due to their association with critical defects, while rounded indications may be acceptable within certain limits. Therefore, the Liquid Penetrant Test method is an effective and practical technique for detecting surface defects and supporting the improvement of structural quality and safety.